Edukasi Penatalaksanaan Insomnia pada Penderita Hipertensi - Nurul Laili; Binti Muasaroh (Yayasan Inspirasi El Burhani, 2023)
Introduction: Patients with hypertension often complain of dizziness/headache, sore or heavy neck and insomnia. People who suffer from hypertension have a risk of poor sleep disorders or insomnia. Patients with hypertension cannot sleep well or insomnia due to dizziness, difficulty breathing, noise and difficulty starting to sleep. Objective: The purpose of this public service activities is to provide education about how to reduce insomnia in people with hypertension so that their sleep quality is better. Method: This public service was conducted by measuring the level of insomnia in patients with hypertension using the Insomnia Severity Index (ISI) questionnaire. The activity was carried out for 2 days on 9-10 September 2022 in the working area of the Bendo Health Center, Kediri Regency. The counseling participants totaled 27 people. After the assessment is carried out, then proceed with providing counseling or education about the management of insomnia experienced by people with hypertension. Result: The results of the interview showed that most of the people (44%) as many as 12 people had good knowledge. The level of education is one of the sociocultural factors that can affect a person's knowledge and understanding of information. A high level of education can enable individuals to access and understand information about health so that someone who has the knowledge to choose strategies in overcoming insomnia. If a person's level of education is low, it will hinder the development of a person's attitude towards receiving information and newly introduced values. Conclusion: Nurses as health workers who play a role in promotive functions, try to do prevention through education so that complications do not continue and get worse. Efforts to overcome insomnia by means of reflexology, relaxation techniques, changing sleep/wake schedules, drinking milk before bed and avoiding nap habits. The family plays an active role in providing motivation, supervision and assistance to a family member who suffers from chronic diseases such as hypertension.